Manajemen Strategi dalam Membudayakan Literasi bagi Dosen dan Mahasiswa di Program Studi Ilmu Perpustakaan dan Informasi Islam IAIN Curup - Taniasari Rahmawati; Yanto, Murni; Sumarto (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
The Islamic Library and Information Science Study Program is a study program that focuses on developing information literacy and management. However, these efforts are often hindered by low reading interest and students’ tendency to access information instantly without engaging with academic sources. On the other hand, lecturers have taken individual initiatives to promote literacy activities. This study employs a qualitative approach with a case study method, involving the head of the department, lecturers, and students as subjects. Data were collected through observation, interviews, and documentation. The findings reveal that literacy development strategies follow the Wheelen and Hunger model, formulated through the institution’s VMTS (Vision, Mission, Targets, and Strategy), although not formally documented. Implementation is participatory through self-initiated activities and informal evaluation, but faces challenges such as the absence of written strategies, weak policy support, and lack of systematic evaluation. The strategy is carried out in three stages: habituation (15-minute reading and storytelling), development (analysis, reviews, exploration of academic sources and information technology), and learning (scientific writing, discussions, and research). This strategic management has positively impacted literacy awareness, independent learning, and critical thinking skills.